Implementasi Pengelolaan Dana Otonomi Khusus Papua Sektor Kesehatan Kabupaten Paniai (Studi Fenomenologi) - Aprianto Lalang Kuddy; Hesty Theresia Salle (Universitas Cenderawasih, 2021)
The aims of this study were to (1) reveal how the local government of Paniai Regency carries out their process of managing special autonomy fund for health sector which consists of planning, budgeting, performing, reporting and evaluating their programs and activities; (2) asses the effectiveness of delivering programs and activities from health agencies of Paniai regency to societies under the mandate of PERDASUS 25/2013. Thus, the population was Paniai local government agents in Health sector. This study employed descriptive analysis, trend analysis, frequency, and percentage for the quantitative data while the qualitative data collected from conducting in-depth interviews and observations. To analyze the data collected, a content analysis and documents from Special Autonomy Fund planning and management was used. One of the evident findings was that in implementing programs and activities under the Special Autonomy Fund in Health sector, the government of Paniai regency was not yet fully comply with required regulations.